2015
DOI: 10.1097/brs.0000000000000869
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of the US FDA IDE Prospective, Randomized Controlled Clinical Trial Comparing PCM Cervical Disc Arthroplasty With Anterior Cervical Discectomy and Fusion

Abstract: 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
224
5
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(239 citation statements)
references
References 22 publications
6
224
5
4
Order By: Relevance
“…Similar observations were verified in a number of studies, which demonstrated comparable post-operative scores at different long-term observation periods, ranging between 4 and 30 years, and irrespective of the type of prosthesis used [2][3][4][16][17][18][19].…”
Section: Long-term Follow-up Of Clinical Outcome Parameterssupporting
confidence: 81%
See 3 more Smart Citations
“…Similar observations were verified in a number of studies, which demonstrated comparable post-operative scores at different long-term observation periods, ranging between 4 and 30 years, and irrespective of the type of prosthesis used [2][3][4][16][17][18][19].…”
Section: Long-term Follow-up Of Clinical Outcome Parameterssupporting
confidence: 81%
“…These findings can, however, no longer be upheld based on the data from current comparative long-term studies, as previously published RCTs demonstrated statistically significantly superior clinical results for the cTDR group in comparison to the patients treated with ACDF [3,4]. As an explanation for these findings, the significantly lower longterm revision rates, especially at the adjacent segment, should be taken into consideration.…”
Section: Long-term Follow-up Of Clinical Outcome Parametersmentioning
confidence: 86%
See 2 more Smart Citations
“…A meta-analysis can help detemine whether this aspiration will come to fruition. A number of intermediate-term trials [5][6][7][8][9][10] have suggested an increased rate of reoperation and poor health-related quality of life outcomes with anterior cervical discectomy and fusion when compared to cervical disc replacement. However, these findings have not been consistent.…”
mentioning
confidence: 99%